SEPEDA MOTOR SEBAGAI METAFORA POLA ASUH OTORITER TERHADAP LINGKUNGAN SOSIAL DALAM KARYA SENI LUKIS REALIS KONTEMPORER - Dra. Jupriani, M.Sn., HARY JUMALINDRA, Drs. Syafwan, M.Si., (Serupa The Journal of Art Education, 2018)
This final work examines the effects of authoritarian parenting patterns that parents apply to children who are brought to the motorcycle and then visualized in contemporary realist painting.The purpose of the creation of this final paper to visualize motorcycles as a metaphor of authoritarian parenting for the environment as well as in this work will be specifically for the authors of the author himself will be used as a visual language about the author's response to an authoritarian parenting style treated.The method of creating works of art, using five stages of preparationÂ  stage, elaboration stage, synthesis stage, stage of concept, realization and completion stage and the last to hold the final work exhibition. In the creation of works, the author uses acrylic paint on canvas with brush stroke technique and uses colors that match the actual object color.Ten masterpieces made representing the theme in the toll tells the story of the expression of a child raised by parents by using authoritarian parenting that affects the child's behavior, mental stress, even some children who suffer from bipolar.Keywords: authoritarian parenting, painting, contemporary realist.